Cloning and Overexpression of Alkaline Phosphatase PhoK from Sphingomonas sp. Strain BSAR-1 for Bioprecipitation of Uranium from Alkaline Solutions - Nilgiriwala, Kayzad S. (American Society for Microbiology (ASM), 2008)
Cells of Sphingomonas sp. strain BSAR-1 constitutively expressed an alkaline phosphatase, which was also secreted in the extracellular medium. A null mutant lacking this alkaline phosphatase activity was isolated by Tn5 random mutagenesis. The corresponding gene, designated phoK, was cloned and overexpressed in Escherichia coli strain BL21(DE3). The resultant E. coli strain EK4 overexpressed cellular activity 55 times higher and secreted extracellular PhoK activity 13 times higher than did BSAR-1. The recombinant strain very rapidly precipitated >90% of input uranium in less than 2 h from alkaline solutions (pH, 9 ± 0.2) containing 0.5 to 5 mM of uranyl carbonate, compared to BSAR-1, which precipitated uranium in >7 h. In both strains BSAR-1 and EK4, precipitated uranium remained cell bound. The EK4 cells exhibited a much higher loading capacity of 3.8 g U/g dry weight in <2 h compared to only 1.5 g U/g dry weight in >7 h in BSAR-1. The data demonstrate the potential utility of genetically engineering PhoK for the bioprecipitation of uranium from alkaline solutions.